Real-time whole genome sequencing to control a Streptococcus pyogenes outbreak at a national orthopaedic hospital. Issue 1 (September 2019) - Sharma, H.; Ong, M.R.; Ready, D.; Coelho, J.; Groves, N.; Chalker, V.; Warren, S.
Summary: Background: Whole genome sequencing (WGS) of Streptococcus pyogenes linked to invasive disease has been used to identify and investigate outbreaks. The clinical application of WGS in real-time for outbreak control is seldom employed. Aims: A fatal case of bacteraemia at a national orthopaedic hospital prompted an outbreak investigation to identify carriers and halt transmission using real-time WGS. Methods: Retrospective surveillance was conducted to identify patients with Streptococcus pyogenes infections in the last year. Upon contact tracing, four patients and 179 staff were screened for Streptococcus pyogenes carriage. All isolates identified were emm -typed. WGS was performed in real-time on a subset of isolates. Findings: Twelve isolates of Streptococcus pyogenes from the index case, two patients and eight staff were identified. Six isolates were emm 1.0, including the index case and five staff isolates. The remaining isolates belonged to distinct emm types. WGS analysis was undertaken on the six emm 1.0 isolates. Five were indistinguishable by single nucleotide polymorphism (SNP) analysis, with 0 SNP distance, and one had one SNP difference, supporting the hypothesis of recent local transmission. All screen-positive healthcare workers were offered treatment with penicillin or clindamycin. No further cases were identified. Conclusion: The increased molecular discrimination of WGS confirmed the clustering of these cases and the outbreak was contained. This demonstrates the clinical utility of WGS in managing outbreaks of invasive Streptococcus pyogenes in real-time and we recommend its implementation as a routine clinical service.